The Relationship Between Prostate Volume and IPSS Score in BPH Patient at the Siti Khodijah Muhammadiyah Cabang Sepanjang Hospital - Putra, Muslim Andala; Waskita, Shakina Reza; Mochtar, Nur Mujaddidah; Himawan, Budi (Universitas Muhammadiyah Surabaya, 2024)
Benign Prostatic Hyperplasia (BPH) is the growth of non-malignant cells or hyperplasia of prostate tissue which causes LUTS in men. One system to assess the symptoms of obstruction due to prostate enlargement is the International Prostate Symptom Score (IPSS). Prostate volume is performed to check the progress of BOO (Bladder Outlet Obstruction) using Transabdominal Ultrasound. This research is an analytical observational study with a prospective cohort method. The sample selection in this research applied consecutive sampling techniques using predetermined inclusion and exclusion criteria. The number of samples used was 30 patients in the period between November 2022 and April 2023. The results showed that the prostate volume in grade II was 46.7%, while for grade I was 33.3% and grade III was 20%. For the results of the IPSS, the moderate category was 76.7%, with mild and severe IPSS scores are 10% and 13.3%. The Spearman test results showed that the p-value was 0.006 <0.05, the value of r = 0.486, and the correlation coefficient was positive, which means that there is a fairly strong relationship between prostate volume and IPSS score in BPH patients at the Siti Khodijah Muhammadiyah Cabang Sepanjang Hospital.